Comparison of genetic and morphological methods to detect the presence of American lobsters, Homarus americanus H. Milne Edwards, 1837 (Astacidea: Nephropidae) in Norwegian waters - Jørstad, K.E.; Prodöhl, Paulo; Agnalt, A.-L.; Hughes, Maria; Farestveit, E.; Ferguson, Andrew (2007)
American lobsters (Homarus americanus H. Milne Edwards, 1837) are imported live to Europe and should according regulations be kept in land-based tanks until sold. In spite of the strict regulations aimed specifically at preventing the introduction of this species into the NE Atlantic, several specimens of H. americanus have been captured in the wild, especially in Oslofjord, Norway since 1999. One of the great concerns is interbreeding between the introduced American species and the local European lobster, H. gammarus (Linnaeus, 1758). For this reason an awareness campaign was launched in 2000 focusing on morphologically "unusual" lobsters caught in local waters. Morphological characters have been based on colour and sub-ventral spines on the rostrum. Two samples of H. americanus were used for comparisons, as well as samples of European lobster from Oslofjord collected in 1992. Previous genetic analyses (allozymes, mtDNA and microsatellite DNA) have demonstrated that the American lobster is distinct from its European counterpart, with several additional alleles at many loci in addition to different allelic frequency distribution of alleles of "shared" alleles. During the present study, thirteen microsatellite loci were tested in the initial screening, and the three most discriminating loci (Hgam98, Hgam197b and Hgam47b) were used in a detailed comparison between the two species. A total of 45 unusual lobsters were reported captured from Ålesund (west) to Oslofjord (southeast) from 2001 to 2005 and these were analysed for the three microsatellite loci. Nine specimens were identified as American lobsters. Comparisons between morphological and genetic characteristics revealed that morphological differences are not reliable in discrimination the two species, or to identify hybrids. Further, some loci display almost no overlapping in allele frequency distribution for the reference samples analysed, thus providing a reliable tool to identify hybrids.